Space Programming as an Approach to Produce Recommendation of Virtual Wayfinding Design Guidelines in Puskesmas - Chadijah, Siti; Fanthi, Reno; Latif, Fauzia; Kumoratih, Dewi (Jurnal Desain Interior, 2024)
Health facilities in Jakarta are facing several challenges to enhance their services, especially addressing the space limitation. One of the vital facilities needed to be provided is space programming and wayfinding to help health facilities improve their service such as separating health patients and patient with unhealthy condition. In fact, there is a lack of information regarding the flow of activities that visitors must go through while visiting the health facility. Provision of information on this flow of activity still depends on the availability of officers. This study provides a recommendation for a better space development of the community health facility as well as more adequate information on the health facilities in Jakarta. Gibson (2009) has encapsulated which types of wayfinding can perform well in indoor areas. Based on the types, this research aims to unravel the limitations of information and provide appropriate access for users. The research was conducted through data collection of facilities and activities in Puskesmas. Space limitations can be resolved by providing accessible and easily understood information. Moreover, the result provides data of information that can be developed on an integrated virtual wayfinding design to achieve efficiency and sustainability in health services.